2017
DOI: 10.1186/s12872-017-0594-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding heart failure; explaining telehealth – a hermeneutic systematic review

Abstract: BackgroundEnthusiasts for telehealth extol its potential for supporting heart failure management. But randomised trials have been slow to recruit and produced conflicting findings; real-world roll-out has been slow. We sought to inform policy by making sense of a complex literature on heart failure and its remote management.MethodsThrough database searching and citation tracking, we identified 7 systematic reviews of systematic reviews, 32 systematic reviews (including 17 meta-analyses and 8 qualitative review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
245
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(255 citation statements)
references
References 112 publications
(210 reference statements)
10
245
0
Order By: Relevance
“…This principle was illustrated in a recent hermeneutic review of telehealth in heart failure by one of us 43. It identified 7 systematic reviews of systematic reviews, 32 systematic reviews (including 17 meta‐analyses) covering hundreds of primary studies, as well as six mega‐trials—almost all of which had concluded that more research (addressing the same narrow question with yet more randomised trials intended to establish an effect size for telehealth) was needed.…”
Section: Systematic or Narrative Or Systematic And Narrative?mentioning
confidence: 99%
“…This principle was illustrated in a recent hermeneutic review of telehealth in heart failure by one of us 43. It identified 7 systematic reviews of systematic reviews, 32 systematic reviews (including 17 meta‐analyses) covering hundreds of primary studies, as well as six mega‐trials—almost all of which had concluded that more research (addressing the same narrow question with yet more randomised trials intended to establish an effect size for telehealth) was needed.…”
Section: Systematic or Narrative Or Systematic And Narrative?mentioning
confidence: 99%
“…Moreover, the complex literature on telehealth also seems marked by methodological issues, like publication bias and poor recruitment in clinical trials. 45 For example, in the TELE-HF study, 14 % of patients assigned to telemonitoring never used the system and by the final week of the study period, only 55 % of the patients were still using the system at least three times a week. 33 As an appropriate adherence to a given intervention can contribute to an adequate external validity of the studies, improvement of adherence represents a key element of the future research on telehealth.…”
Section: Hf-related Hospitalisations the Recent Better Effectivenessmentioning
confidence: 99%
“…patients under 65 years of age), whereas in other subgroups (patients with moderate or severe depression), involvement in self-management may be even associated with a reduced survival rate. 45 Again, careful stratification of patients enrolled in clinical studies seems to be a pivotal pre-requirement for a valuable application of telehealth to different healthcare contexts.…”
Section: Patient Participationmentioning
confidence: 99%
“…For example, increased workload is a common factor for poor uptake of new health technologies [14,15,[18][19][20][21][22]. In this study, PCPs anticipated an increase in workload, particularly in the initial stages of implementation, and argued that their acceptance of this increase was contingent on the perceived benefit of the app for the patient.…”
Section: Comparison With Prior Workmentioning
confidence: 89%
“…Research suggests that their effectiveness is often limited by poor uptake and sustained use by health care providers [18,19]. Recent systematic reviews have suggested that key barriers for health care providers are increased workload, and disruption to existing clinical processes and staff roles as well as concerns about remuneration, data security and liability [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%